HistoryDB - Melendez-Colom, Eda, author; Kaplan, Nicole, author; Baker, Karen, author; Wiley, Sean, author; Petersen, Robert I., author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2009)
Organizational history requires a facility to manage, archive and present event details as well as narratives that provide perspective to the events. While events form a historical thread, storied narratives weave these threads together into a retrospective. The LTER Information Management Committee has recognized that working collaboratively to understand their history is a tool for exploring how they function within the LTER organizational structure. Such a tool provides valuable input to the development of governance procedures for community-level efforts.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Colorado State University. Natural Resource Ecology Laboratory; Colorado State University. Department of Forest and Rangeland Stewardship; Colorado State University. Department of Soil and Crop Sciences; Colorado State University. Department of Biology; California State University, Fullerton; United States. Agricultural Research Service; University of Northern Colorado; CCE-LTER; Ocean Informatics.
Keywords: shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland; long term ecological research; grassland ecology